2019
DOI: 10.1038/s41385-019-0178-9
|View full text |Cite
|
Sign up to set email alerts
|

SARI attenuates colon inflammation by promoting STAT1 degradation in intestinal epithelial cells

Abstract: SARI functions as a suppressor of colon cancer and predicts survival of colon cancer patients, but its role in regulating colitis has not been characterized. Here we show that SARI −/− mice were highly susceptible to colitis, which was associated with enhanced macrophage infiltration and inflammatory cytokine production. Bone marrow reconstitution experiments demonstrated that disease susceptibility was not dependent on the deficiency of SARI in the immune compartment but on the protective role of SARI in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
4
11
0
Order By: Relevance
“…According to the present findings and our previous study, 18 we hypothesize that SARI impairs CAC through attenuating colitis by directly targeting and promoting protease-dependent degradation of STAT1 and the transcriptional activity of STAT1/MCP-1 (Figure 8).…”
Section: Sari Directly Targets and Inhibits Stat1 Expression In Colsupporting
confidence: 86%
See 2 more Smart Citations
“…According to the present findings and our previous study, 18 we hypothesize that SARI impairs CAC through attenuating colitis by directly targeting and promoting protease-dependent degradation of STAT1 and the transcriptional activity of STAT1/MCP-1 (Figure 8).…”
Section: Sari Directly Targets and Inhibits Stat1 Expression In Colsupporting
confidence: 86%
“…CCR2 knockout blocks the SARI deficiency‐promoted tumorigenesis. Furthermore, STAT1 was also proved as the direct target of SARI in colon cancer cells, evidenced by Co‐IP and IF staining, as indicated in intestinal epithelial cells . Other transcriptional regulation factors of MCP‐1, including NF‐κB and STAT3, were up‐regulated in colon tissues of SARI −/− mice in CAC, but demonstrated not to be the direct target of SARI in colon cancer cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Neutrophils and monocytes/macrophages were seen to infiltrate extravascular uveal tissue in LPS‐treated eyes and reached all the structures of interest (ciliary body, anterior, posterior and vitreous chambers, and retina). SARI deficiency caused significant increases of this effect . Conversely, the eyes in all PBS‐injected mice showed very minimal inflammatory changes with an absence of inflammatory cell infiltration in the anterior chamber and posterior segment (Figure 5A & C).…”
Section: Resultsmentioning
confidence: 95%
“…Likewise, a significant growth (82.5%) was also noted in the retina and vitreous chamber in EIU‐SARI −/− group vs. EIU‐SARI WT (Figure 5D). According to the regulation of CCL 2‐positive inflammatory cells infiltration in colon by SARI, we further determined the expression of CCL 2 in extravascular uveal tissue. Our results suggested that SARI deficiency promoted the expression of CCL 2 in EIU model (Figure 5E & F), which indicated that more CCL 2‐positive cells infiltrated the extravascular uveal tissue.…”
Section: Resultsmentioning
confidence: 99%